Comparison of Egg Production Performance and Egg Quality Traits of Pearl and Black Strains of Guinea Fowl in a Humid Rain-Forest Zone of Nigeria - Obike, O.M.; Oke, U.K.; Azu, K.E. (International Journal of Poultry Science, 2011)
Data on 272 eggs collected from Pearl (175 eggs) and Black (97 eggs) adult guinea fowl strains were analyzed to determine the egg production performance and egg quality characteristics of the birds. Data generated were analyzed using Student’s t-test. The external egg quality traits measured were egg weight, egg length, egg width, shell weight, shell thickness and egg shape index. Internal egg quality traits studied include egg mass, yolk weight, yolk height, yolk diameter, yolk index, albumen weight, albumen height and albumen diameter and albumen index. The production performance traits measured were egg number and Hen-Day Production (HDP). In addition, weekly body weight of the hens was also recorded. Egg number was significantly (p0.05) between HDP of the two strains, the Black strain had higher HDP in all the weeks except in weeks 1, 5 and 6. Among the internal traits, albumen diameter differed significantly (p